2022
DOI: 10.1186/s13020-022-00571-1
|View full text |Cite
|
Sign up to set email alerts
|

Tea and tea drinking: China’s outstanding contributions to the mankind

Abstract: Background Tea trees originated in southwest China 60 million or 70 million years ago. Written records show that Chinese ancestors had begun drinking tea over 3000 years ago. Nowadays, with the aging of populations worldwide and more people suffering from non-communicable diseases or poor health, tea beverages have become an inexpensive and fine complementary and alternative medicine (CAM) therapy. At present, there are 3 billion people who like to drink tea in the world, but few of them actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 106 publications
(124 reference statements)
0
77
0
2
Order By: Relevance
“…The same authors concluded that using 1 g and 10 min only, the levels obtained for the same elements were very similar to those referred to the same extraction time [ 38 ]. From the analysis of our data, it seems that the contribution of tea drink to the daily intake of the elements under study is scarce despite the phytochemical profile of different teas with relative antioxidant and anti-inflammatory capacities has been clearly shown [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same authors concluded that using 1 g and 10 min only, the levels obtained for the same elements were very similar to those referred to the same extraction time [ 38 ]. From the analysis of our data, it seems that the contribution of tea drink to the daily intake of the elements under study is scarce despite the phytochemical profile of different teas with relative antioxidant and anti-inflammatory capacities has been clearly shown [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…recently published a meta-analysis and systematic review also showing that increasing one cup of tea per day reduces the incidence of oral cancer by 6.2%. More than 100 chemical components have been isolated and identified from oolong tea, among which polyphenols are the most significant ones ( 23 , 24 ). The polyphenols contain multiple functional components, such as (-)-epigallocatechin gallate (EGCG) and theaflavin (TF) ( 25 , 26 ), which were reported to have anti-inflammatory and antioxidant effects, and other biological properties ( 5 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that approximately 2.5 million tons of tea leaves are produced worldwide annually, of which 20% are produced as green tea, mainly consumed in Asia, parts of North Africa, the United States, and Europe [ 14 ]. The association between tea consumption, particularly green tea, and human health has long been recognized [ 46 , 47 ]. Green tea contains polyphenols, including flavanols, flavanediols, flavonoids, and phenolic acids.…”
Section: Discussionmentioning
confidence: 99%